Body mass center travel trajectory analysis for ko-uchi-gari in judo bouts - Levitsky, A. G.; Matveyev, D. A.; Potsipun, A. A.; Oshina, O. V. (Theory and Practice of Physical Culture, 2019)
Subject to the study was the attacked athlete`s (Uke) body mass center travel trajectory analysis for the back heel action in judo bouts - to rate the attacker`s (Tori) action efficiency and profile the movement biomechanics, and to improve the technique and find an ideal execution pattern. The article analyzes the body mass center travel trajectory for the back heel action (Ko-Uchi-Gari) in judo bouts using video captures and a frame-by-frame analysis of body mass center movement. Mass centers of every key body segment were computed to find the athlete`s body mass center in every frame. The study data and analysis showed that the Uke`s body mass center was rotated prior to the back heel action. Therefore, it may be beneficial to have the training systems complemented by the prior Uke rotation mastering exercises to effectively model the competitive situations. The study findings may be used to improve the judo/ sambo training systems in university groups, children and youth sport schools and youth sport clubs.